Non-Suicidal Self-Injury (NSSI) in Borderline Personality Disorder: Dynamic Mechanisms, Cascading Models, and Psychosocial Outcomes in the Context of Specialist Interventions - Protsenko, Yuliia; Barczewska, Magdalena; Marczak, Anna; Kowalska, Marta; Bieszczad, Dominika; Musialska, Zuzanna; Stadnicka, Olga; Opalińska-Kubowicz, Marta; Swojnóg, Marzena; Mazurek, Adam; Popielarska, Kinga; Andrzejewska, Julia (Quality in Sport, 2026)
Background. Non-suicidal self-injury (NSSI) occurs in 69-90% of women with borderline personality disorder (BPD) and represents a critical diagnostic criterion and therapeutic challenge. Despite its high prevalence and clinical significance, the dynamic psychological and neurobiological mechanisms underlying NSSI remain incompletely understood, and a substantial gap persists between acute symptom reduction and long-term psychosocial recovery. Aim. This study reviews NSSI in BPD, focusing on: identification of proximal psychological mechanisms and developmental factors influencing NSSI risk, and assessment of specialized therapeutic approaches' effectiveness in reducing NSSI and achieving sustained psychosocial functioning. Materials and Methods. A literature review was conducted using databases (PubMed, PsycINFO, and Google Scholar) for articles up to November 2025. Inclusion criteria focused on peer-reviewed studies examining NSSI in BPD populations using validated assessment tools. Results. Neuroimaging demonstrates that NSSI produces immediate amygdala deactivation, providing neurobiological reinforcement for this behavior. The Emotional Cascade Model identifies rumination instability and emotion differentiation deficits as key triggers for NSSI episodes. Childhood trauma dysregulates the HPA axis and correlates with functional deficits. Dialectical Behavior Therapy (DBT) shows a moderate effect size in reducing self-harm (Hedges' g = -0.622) and induces neuroplastic changes. Mentalization-Based Therapy (MBT) reduces suicide attempts, though social functioning often remains impaired even in long-term follow-up. Conclusions. Specialized psychotherapies effectively stabilize acute symptoms, but a clear gap persists between symptom control and functional recovery. Future research should adopt complex dynamic systems perspectives and prioritize outcomes reflecting social integration and quality of life.